Malaysia Road Safety Performance Indicators: Experts Perspectives - I. S. M. Razelan; R. A. Rahman; A. Ismail; N. F. Mohd Ali (Journal of the Society of Automotive Engineers Malaysia, 2022)
Realizing the need to halve the number of crashes and deaths caused by road traffic crashes, every road safety expert in all countries has been working hand in hand with various related agencies to develop solutions, planning programs, and strategic planning. Malaysia is also included in this scenario. Data from various countries on performance indicators and law enforcement procedures that may directly impact the severity of the issues between Malaysia with other low and middle-income countries and between several high-income countries were scrutinized. It was found that Malaysian law and regulations standards are not far behind those low, middle, and high-income countries, proving that Malaysia has have done its best to manage road safety issues. To further conclude the underlying issues on road safety in Malaysia as a basis for the Malaysian Road Safety Performance Index framework, questionnaires were distributed to the Malaysian road safety expert network. The analysis found that Road Conditions and Drivers Characteristics were selected as the most critical pillars that need to be further scoured. These two factors hold the most basic indicators representing a bigger picture of Malaysia's road safety issues.